Respuesta :

f - 1 is the answer because f - 1x take the one away and f - x is all there's left 

Answer:

[tex]f^{-1}(x)[/tex]= [tex]\frac{1}{4x-12)}[/tex].

Step-by-step explanation:

Given  : f(x) = [tex]\frac{1}{4x}+3[/tex].

To find : inverse

Solution : We have given f(x) = [tex]\frac{1}{4x}+3[/tex].

Step 1: f(x) = y

y =  [tex]\frac{1}{4x}+3[/tex].

Step 2: replace x and y .

x =  [tex]\frac{1}{4y}+3[/tex].

Step 3:

Solve for y

On subtracting both sides by 3

x -3  = [tex]\frac{1}{4y}[/tex].

Taking reciprocal both sides

4y =  [tex]\frac{1}{x-3}[/tex].

On dividing both sides by 4

y =  [tex]\frac{1}{4(x-3)}[/tex].

Take [tex]f^{-1}(x)=y[/tex].

[tex]f^{-1}(x)[/tex]= [tex]\frac{1}{4(x-3)}[/tex].

Therefore,  [tex]f^{-1}(x)[/tex]=[tex]\frac{1}{4x-12}[/tex].